Problems and contradictions of international migration statistics - B. B. Loginov (Управление)
Analysis of problems and trends in the field of international migration development is impossible without reliable statistical data. Particular economic importance for any country including Russia are data on the flows of labor migrants, which have a great impact on the domestic labor market, gross domestic product, balance of payments. International organizations, including United Nations bodies, haven’t worked out single recommendations on proceeding migration statistics, stratification of migration flows. The universal worldwide technique with border and internal migrant calculation principles regarding flows and stocks of labor migrants is absent at the moment.The author focuses on key discrepancies of national migration statistics in different countries and widely practiced flexible interpretation of it by Western politicians and mass media, therefore, the acuteness of migration problems in the Western countries (first, in the European Union) is overestimated and, on the contrary, migration difficulties of such countries as Russia, Iran, Turkey are downgraded or fully ignored. The difficulties in the calculation of international migration, arising from the ambiguous interpretation of the concept of “migrant”, have been indicated. Three approaches – residence outside the country of birth, citizenship, place of usual daily rest – often conflict with each other, when it is necessary to establish the true country of origin of the migrant.The shortcomings of the main sources of information about immigrants: population census, administrative records, population surveys have been also analyzed in the article. New phenomena in international migration flows, such as “cross-motivation” of migrants and migration without going abroad, require their understanding.